2015
DOI: 10.1007/s00345-015-1585-5
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-mini PCNL versus flexible ureteroscopy: a matched analysis of analgesic consumption and treatment-related patient satisfaction in patients with renal stones 10–35 mm

Abstract: Treatment of medium- to large-sized renal stones is safe and highly effective by both UMP and fURS. Moreover, both treatments yield comparable postsurgical analgesic requirements and high patient satisfaction scores. Patient-related factors (anatomical and stone related) and availability of technical equipment and surgical expertise appear to be the most important determining factors in treatment planning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
44
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 15 publications
5
44
2
Order By: Relevance
“…All studies expect Wilhelm [24] indicated that RIRS resulted in shorter hospital stays compared with MIPPs. Again, reasons underlying this may be similar to those proposed for the analysis of hemoglobin levels.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…All studies expect Wilhelm [24] indicated that RIRS resulted in shorter hospital stays compared with MIPPs. Again, reasons underlying this may be similar to those proposed for the analysis of hemoglobin levels.…”
Section: Discussionmentioning
confidence: 99%
“…All studies included were full-text articles. Among all the studies, RIRS was compared with mini-PCNL in six studies [14][15][16][17][18][19], micro-PCNL in three studies [20][21][22], ultra-mini PCNL in two studies [23,24], and mixture of mini and micro PCNL in one study [25]. Agreement between the two reviewers was 91.67% for quality assessment of articles.…”
Section: Evidence Synthesismentioning
confidence: 99%
See 2 more Smart Citations
“…This new treatment modality seems to be promising for the management of middle-sized stones; however, up to now only a few studies have been published from certain centers reporting the limited number of experiences of the same few surgeons. [10][11][12][13][14][15][16] We report herein the outcomes of the prospective clinical study of UMP compared with the findings cited in the literature. With the surgeons' increased experience using UMP and presentation of series, the role of UMP in the management of renal stones will be more clearly understood.…”
Section: Introductionmentioning
confidence: 99%